The developing students' dicipline character - Dewi Rahmi; Maria Mentessori; Isnarmi Moeis (Jurnal Aplikasi IPTEK Indonesia, 2018)
This study have some purposes. First, to analyze the implementation of developing dicipline students' character in school. Second, to analyze the school strategies in maintaining the developing character of students' discipline. Third, to identify obstacles in fostering the character of students' discipline. Fourth, to found a solution in fostering the character of students' discipline. Meanwhile, this research used qualitative method by using interview technique, observation and documentation study. The results of this study indicate that the implementation of students' discipline character is seen at the students who come late in school, the rules enforced by the school adhered to all participants in the school, is not independent of the school's character education is well developed through a supportive school culture. School strategy in maintaining the character of student discipline is by providing motivation, encouraging students to obey the rules through banners displayed in every corners of the school and apply reward and punishment system. Meanwhile, the constraints that face for this problem are often encountered in school in the formation of student discipline character that is the delay of students coming to school and lack of parental support in disciplining children. Hence, as the solving of problem, the school giving some advice to the student's about to don't come to school and also make a cooperation solution with student's parent by sent letter, that called warning letter. Then, by the cooperation with the parent could to overcome the students' dicipline problem.